Global Wine Markets, 1961 to 2009: A statistical compendium - Anderson, Kym (University of Adelaide Press, 2011)
Until very recently, most grape-based wine was consumed close to where it was produced, and mostly that was in Europe. Barely one-tenth of the world's wine production was exported prior to the 1970s, even counting intra-European trade. The latest wave of globalization has changed that forever. Now more than one-third of all wine consumed globally is produced in another country, and Europe's dominance of global wine trade has been greatly diminished by the surge of exports from 'New World' producers. New consumers also have come onto the scene as incomes have grown, eating habits have changed and tastes have broadened. Asia in particular is emerging as a new and rapidly growing wine market - and in China that is stimulating the development of local, modern production capability that, in volume terms, already rivals that of Argentina, Australia and South Africa. This latest edition of global wine statistics therefore not only updates data to 2009 and revises past data, but also expands on earlier editions in a number of ways. For example, we now separately identify an extra eight Asian countries or customs areas (Hong Kong, India, Korea, Malaysia, Philippines, Singapore, Taiwan and Thailand) in addition to China and Japan. We also include more than 50 new tables to cover such items as excise and import taxes, per capita expenditure on wine, the share of domestic sales in off-trade, the shares of the largest firms in national markets and globally, and the most powerful wine brands globally. Given the growing interest in the health aspects of alcohol consumption, we now express it per adult as well as per capita. Perhaps the most significant addition to this latest version is a new section that provides estimates of the volume, value and hence unit value of wine production, consumption, exports and imports for four catagories: sparkling wines, and non-premium, commercial-premium and super-premium still wines.